Allelopathic effect of sorghum root extract and its potential use as a bioherbicide - Setyowati, N.; Nurjanah, U.; Utami, R. S.; Muktamar, Z.; Fahrurrozi, F. (International Journal of Agricultural Technology, 2021)
The bioherbicide of sorghum root extract had a significant effect on seed germination. It inhibited the seedling growth of test plants, i.e., rice (Oryza sativa) and mung bean (Vigna radiata). The test plant treatment significantly affected the radicle and plumule length, radicle and plumule fresh weight, and the radicle and plumule dry weight. Bioherbicide concentration, on the other hand, affected all observed variables i.e. normal and abnormal sprouts, radicle and plumule length, and radicle and plumule weight. The percentage of normal and abnormal sprouts, radicle and plumule length, and radicle fresh weight correlated with the test plant and bioherbicide concentration. The higher the concentration of sorghum root extract, the lower the normal sprouts, radicle length, plumula length, and the fresh weight of mung bean (representing broad-leaf weed) and rice (representing narrow-leaf weeds). The regression analysis showed that LC 50% sorghum root extract was 5.24% for rice and 4.93% for mung bean. In summary, sorghum root extract can be a bioherbicide to control both narrow and broadleaf weeds in marginal land of coastal environment.